Reiki as a support to nursing care for the emotional suffering of cancer patients (Research, Society and Development, 2021)
Objective: To analyze and describe the effectiveness of reiki as a mechanism to alleviate the suffering of cancer patients, to collect effective data for the introduction of therapy in the daily lives of patients affected by malignant neoplasms and to advocate the use of reiki for complementary treatment of cancer patients. Method: Exploratory integrative review on the effects of Reiki on cancer patients. The bibliographic survey for the study was carried out electronically, through the databases contained in the VHL. The descriptors used were: Complementary therapy; Oncology, with Boolean operator AND. Results: Three cross-sectional studies, from 2016 to 2021, in English and Portuguese were analyzed, where they listed the symptoms presented before therapy and compared them with the reports provided by patients after application. In all studies, patients achieved significant improvement. Conclusion: Reiki therapy is effective for relieving psychoemotional symptoms in cancer patients or not, as it holistically visualizes them while respecting their pandimensional aspects.